2021
DOI: 10.1101/2021.02.03.429616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PML-Dependent Memory of Type I Interferon Treatment Results in a Restricted Form of HSV Latency

Abstract: Herpes simplex virus (HSV) establishes latent infection in long-lived neurons. During initial infection, neurons are exposed to multiple inflammatory cytokines but the effects of immune signaling on the nature of HSV latency is unknown. We show that initial infection of primary murine neurons in the presence of type I interferon (IFN) results in a form of latency that is restricted for reactivation. We also found that the subnuclear condensates, promyelocytic leukemia-nuclear bodies (PML-NBs), are absent from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 104 publications
(148 reference statements)
0
6
0
Order By: Relevance
“…It has previously been reported that quiescent genomes exist in multiple states with respect to activation of viral genes and that there is a relatively large proportion of genomes in primary mouse trigeminal neurons that is not stringently repressed (Terry‐Allison et al , 2007). Suzich and co‐workers now show that HSV latency represents multiple states with respect to repression and the ability to reactivate, and they provide a model to explain this phenomenon (Fig 1) (Suzich et al , 2021). They suggest a scenario in which infection of a naïve sensory neuron can establish latency that is more reactivatible, possibly maintained in the latent state by the polycomb repressor complexes PRC1/PRC2 as previously described (reviewed in Watson et al , 2013).…”
Section: Figure Multiple Types Of Hsv Latency Programmes Are Maintained Epigenetically Depending On the State Of The Cells At The Time Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…It has previously been reported that quiescent genomes exist in multiple states with respect to activation of viral genes and that there is a relatively large proportion of genomes in primary mouse trigeminal neurons that is not stringently repressed (Terry‐Allison et al , 2007). Suzich and co‐workers now show that HSV latency represents multiple states with respect to repression and the ability to reactivate, and they provide a model to explain this phenomenon (Fig 1) (Suzich et al , 2021). They suggest a scenario in which infection of a naïve sensory neuron can establish latency that is more reactivatible, possibly maintained in the latent state by the polycomb repressor complexes PRC1/PRC2 as previously described (reviewed in Watson et al , 2013).…”
Section: Figure Multiple Types Of Hsv Latency Programmes Are Maintained Epigenetically Depending On the State Of The Cells At The Time Ofmentioning
confidence: 99%
“…Suzich et al (2021) now elegantly demonstrate that the latent HSV genome can exist in multiple states with respect to reactivation that are a function of the presence of PML‐NBs. PML‐NBs have been shown to result in the deposition of histone H3.3 modified on lysine 9 by trimethylation (H3K9me3), and in the absence of PML, there is a shift versus H3K27me3 (Delbarre et al , 2017).…”
Section: Figure Multiple Types Of Hsv Latency Programmes Are Maintained Epigenetically Depending On the State Of The Cells At The Time Ofmentioning
confidence: 99%
See 3 more Smart Citations